2021
DOI: 10.1108/ejtd-08-2020-0127
|View full text |Cite
|
Sign up to set email alerts
|

Do “decent work” dimensions lead to work engagement? Empirical evidence from higher education institutions in India

Abstract: Purpose The study aims to investigate the impact of “decent work” dimensions on faculty members’ work engagement levels in the higher education institutions in India. Design/methodology/approach Data were obtained from 293 faculty members working in higher education institutes in India. The proposed study hypotheses were tested by deploying the statistical technique of multiple regression analysis using statistical package for social sciences Version-24. Findings Results demonstrated that of the five dimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 75 publications
(134 reference statements)
1
8
0
Order By: Relevance
“…Third, this study reveals the associations of decent work with three important concepts widely used in vocational health psychology, namely job demands, job resources, and work engagement and the findings of this study also support decent work as a distinctive concept from job demands, job resources and work engagement. Consistent with the findings of recent studies ( Kashyap et al, 2021 ; Xu et al, 2022 ) which revealed that decent work was positively associated with work engagement, this study advances our understanding regarding the relationships of decent work with a social recognition component with job demands, job resources, and work engagement. The discriminant validity of decent work in relation to these concepts can help differentiate the psychology of working theory from other perspectives in vocational health psychology.…”
Section: Discussionsupporting
confidence: 91%
“…Third, this study reveals the associations of decent work with three important concepts widely used in vocational health psychology, namely job demands, job resources, and work engagement and the findings of this study also support decent work as a distinctive concept from job demands, job resources and work engagement. Consistent with the findings of recent studies ( Kashyap et al, 2021 ; Xu et al, 2022 ) which revealed that decent work was positively associated with work engagement, this study advances our understanding regarding the relationships of decent work with a social recognition component with job demands, job resources, and work engagement. The discriminant validity of decent work in relation to these concepts can help differentiate the psychology of working theory from other perspectives in vocational health psychology.…”
Section: Discussionsupporting
confidence: 91%
“…The HR literature has consistently highlighted the importance of employee work engagement and high performance work (Aboramadan et al, 2020;Jurek and Besta, 2021;Kashyap et al, 2022). Nevertheless, organizations are facing complex challenges because of the unprecedented crisis of COVID-19, globalization, environmental changes and expectations of high-performance work (Azizi et al, 2021;Jurek and Besta, 2021;Sarkar, 2022).…”
Section: Hr Compensation and Trainingmentioning
confidence: 99%
“…Employee work engagement is defined as employees enthusiasm, high energy, concentration and positive state of mind at the workplace (Anlesinya et al, 2023;Venz et al, 2018). Similarly, there is strong evidence in the literature that HR practices, such as compensation and training, have a direct influence on employee work engagement (Aboramadan et al, 2020;Ferenhof et al, 2015;Jurek and Besta, 2021;Kashyap et al, 2022). The term compensation refers to characteristics that talk about bounces, rewards, financial incentives and growth in salary (Said et al, 2023;Ybema et al, 2020).…”
Section: Hr Compensation and Trainingmentioning
confidence: 99%
See 2 more Smart Citations